Obesity contributes toward hypertension in young and older adult - Pradono, Julianty; Sintawati, Sintawati (Universa Medicina, 2016)
BackgroundObesity and hypertension are independent risk factors in the increasing prevalence of non-communicable diseases. The proportion of obesity in Indonesia has increased in the last 5 years according to the National Health Survey. The purpose of this research was to obtain the contribution of obesity toward hypertension in the age group of 18 years and above.MethodsAn observational study of cross-sectional design was conducted using the National Basic Health Research 2013 population data. The total sample of subjects was 2,741,297 from 33 provinces in Indonesia. Data were collected through interviews, blood pressure measurement, and anthropometry. Analysis of categorical data was by means of the chi-square statistical test, followed by calculation of the attributable fraction in the population, and analysis of factors influencing the impact fraction.ResultsThe prevalence of general obesity (BMI>25 kg/m2) was 31.5% in males and 48.0% in females, while central obesity was 20.9% in males and 42.5% in females. In females with general obesity the risk of hypertension was 1.84 (95% CI: 1.82-1.86) times higher than in those with normal BMI. If general obesity and central obesity can be reduced, the prevalence of hypertension may be reduced by 2.9% in males and by 12.2% in females.ConclusionThe prevalence of hypertension in the age group of 18 years or more can be reduced by 2.9% in males and by 12.2% in females, by overcoming the contribution of obesity. Therefore efforts should be geared towards promoting healthy eating habits and maintaining a healthy weight through health education.